Innovation in organisational control systems: toward greater accountability. (2015) - Martin-Rios, Carlos
Organisational control systems are a central phenomenon, yet despite their significance, top-down command-and-control approaches often dominate research. This surmise creates no problem in hierarchical organisations where everyone knows their work duties and what is expected of them. However, it becomes troublesome in knowledge work, where the sets of tasks carried out by any two members of the organisation differ significantly. The article offers conceptual insights elucidating control systems based on the notion of accountability; which help to raise awareness and mobilise efforts beyond the boundaries of long-established hierarchical control. Implications for the theory and practice of organisational control are discussed.